Hot property in New Zealand: Empirical evidence of housing bubbles in the metropolitan centres. Issue 1 (2nd January 2016) - Greenaway-McGrevy, Ryan; Phillips, Peter C.B.
Abstract : Using recently developed statistical methods for testing and dating exuberant behaviour in asset prices we document evidence of episodic bubbles in the New Zealand property market over the past two decades. The results show clear evidence of a broad-based New Zealand housing bubble that began in 2003 and collapsed over mid-2007 to early 2008 with the onset of the worldwide recession and the financial crisis. New methods of analysing market contagion are also developed and are used to examine spillovers from the Auckland property market to the other metropolitan centres. Evidence from the latest data reveals that the greater Auckland metropolitan area is currently experiencing a new property bubble that began in 2013. But there is no evidence yet of any contagion effect of this bubble on the other centres, in contrast to the earlier bubble over 2003–2008 for which there is evidence of transmission of the housing bubble from Auckland to the other centres. One of our primary conclusions is that the expensive nature of New Zealand real estate relative to potential earnings in rents is partly due to the sustained market exuberance that produced the broad-based bubble in house prices during the last decade and that has continued through the most recent bubble experienced in the Auckland region since 2013.